Regulation of the training process in the athletic preparation of Greco-Roman wrestlers - Laptev, A.I.; Shevtsov, A.V.; Ivanchenko, M.M. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop an algorithm for substantiating management decisions on training load planning, taking into account operational and current control indicators and criteria for the functional condition of Greco-Roman wrestlers. Methods and structure of the study. The following methods were used in the scientific work: accelerometry, pulsometry, cardiointervalometry, lactometry, questioning, pedagogical testing, pedagogical experiment, as well as methods of mathematical statistics. Results and conclusions. Criteria for operational control (daily use) have been identified, including biomechanical and medical-biological markers: time taken to perform 10 throws, throwing power, stability of applied force and rotation when performing a series of throws, subjective assessment of load on the Borg scale, heart rate during sleep, regulatory system stress index. Criteria for ongoing monitoring (within the microcycle) have also been established: lactate level dynamics, regulatory system activity index (PSAI), and rotation efficiency when performing a series of dummy throws.